Role of Hippo-YAP Signaling in Osseointegration by Regulating Osteogenesis, Angiogenesis, and Osteoimmunology - Zhou, Anqi; Yu, Hui; Liu, Jiayi; Zheng, Jianan; Jia, Yinan; Wu, Bingfeng; Xiang, Lin (Frontiers in Cell and Developmental Biology, 2020)
The social demand of dental implantation is growing at a rapid rate, while dentists are faced with the dilemma of implantation failures associated with unfavorable osseointegration. Clinical-friendly osteogenesis, angiogenesis and osteoimmunology around dental implants play a pivotal role in a desirable osseointegration and it’s increasingly appreciated that Hippo-YAP signaling pathway is implicated in those biological processes both in vitro and vivo in a variety of study. In this article we review the multiple effects of Hippo-YAP signaling in osseointegration of dental implants by regulating osteogenesis, angiogenesis and osteoimmunology in peri-implant tissue, as well as highlight prospective future directions of relevant investigation.